Close your eyes or open your mind: Effects of sleep and mindfulness exercises on entrepreneurs' exhaustion - Murnieks, Charles Y.; Arthurs, Jonathan D.; Cardon, Melissa S.; Farah, Nusrat; Stornelli, Jason; Michael Haynie, J. (Journal of Business Venturing, 2020)
Exhaustion is a prominent problem in entrepreneurship because it inhibits cognitive functioning, opportunity identification and evaluation, decision-making, and perseverance. We examine the possible benefits of sleep and mindfulness exercises in reducing the exhaustion experienced by entrepreneurs in the course of launching and growing ventures. Across two studies, we find that both sleep and mindfulness exercises provide avenues for entrepreneurs to combat exhaustion. More interestingly, we find that these two factors compensate for one another; as the usage of one increases, the efficacy of the other decreases. This has important implications for reducing exhaustion and improving cognitive functioning and motivational energy among entrepreneurs.